Modulation of NMDA-Mediated Clock Resetting in the Suprachiasmatic Nuclei of mPer2Luc Mouse by Endocannabinoids - Sládek, Martin; Sumová, Alena (Frontiers in Physiology, 2019)
Light entrains the master circadian clock in the suprachiasmatic nucleus (SCN) predominantly through glutamatergic signaling via NMDA receptors. The magnitude and the direction of resulting phase shifts depend on timing of the photic stimulus. Previous reports based on behavioral and electrophysiological data suggested that endocannabinoids (EC) might reduce the ability of the SCN clock to respond to light. However, there is little direct evidence for the involvement of EC in entrainment of the rhythmic clock gene expression in the SCN. We have used luminescence recording of cultured SCN slices from mPer2Luc mice to construct a complete phase response curve for NMDA receptor activation. The results demonstrated that NMDA administration phase-shifts the PER2 rhythm in a time-specific manner. A stable “singularity", in the course of which the clock seemingly stops while the overall phase is caught between delays and advances, can occur in response to NMDA at a narrow interval during the PER2 level decrease. NMDA-induced phase delays were affected neither by the agonist (WIN 55,212-2 mesylate) nor by the antagonist (rimonabant hydrochloride) of EC receptors. However, the agonist significantly reduced the NMDA-induced phase advance of the clock, while the antagonist enhanced the phase advance, causing a shift in the sensitivity window of the SCN to NMDA. The modulation of EC signaling in the SCN had no effect by itself on the phase of the PER2 rhythm. The results provide evidence for a modulatory role of EC in photic entrainment of the circadian clock in the SCN.